Teachers’ and Students’ Perspectives on the Ethical Use of Artificial Intelligence in Vocational Education using Technology Acceptance Model Approach - Kekado, Nathan Christianto; Krismiyati, Krismiyati (Jurnal Ilmu Komputer dan Informatika, 2025)
Artificial Intelligence (AI) is increasingly integrated into educational settings, offering benefits such as improved efficiency, personalization, and student engagement. However, its adoption also raises ethical concerns that require careful consideration. This study investigates teachers’ and students’ perspectives on the ethical use of AI in vocational education, employing the Technology Acceptance Model (TAM) extended with Ethical Awareness, Trust, and Subjective Norms. A quantitative research design was applied, supported by interviews for triangulation. Data were collected from 60 students and 5 teachers in the Computer and Network Engineering program at SMK Negeri 2 Salatiga, Indonesia, all of whom had prior AI usage experience. The results indicate that Ethical Awareness significantly influences Attitude Toward Use (p = 0.002, t = 3.070), Behavioral Intention (p < 0.001, t = 6.175), and Perceived Usefulness (p < 0.001, t = 4.330). Perceived Ease of Use was found to have a positive effect on Behavioral Intention (p = 0.004, t = 2.913). Trust exhibited a strong relationship with both Actual Use (p < 0.001, t = 3.543) and Attitude Toward Use (p = 0.009, t = 2.621). Reliability testing showed Cronbach’s Alpha values above 0.70 for all key constructs, with Average Variance Extracted (AVE) values exceeding 0.50, indicating strong internal consistency and validity. These findings emphasize that ethical awareness and trust are critical determinants in fostering AI adoption in education. The study provides actionable insights for policymakers, educators, and technology developers to design training programs and guidelines that address ethical considerations, thereby ensuring responsible and sustainable AI integration in educational environments.